(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Bank assets have a direct impact on the liquidity, solvency, scope of operations and, accordingly, the volume of income of a commercial bank. Asset operations of banks increase the objective need for long-term loans, and allows to improve the financial and economic situation of entities.